Everyday life’s changes in spaces of social reproduction: residents’ movements in marginalised neighbourhoods of Santa Cruz de Tenerife (Spain) - Juan Samuel García-Hernández (Boletín de la Asociación de Geógrafos Españoles, 2018)
Since the last decades of the twentieth century there has been a weakening of neighborhood movements in the Spanish urban peripheries. In this temporal context, through documentary analysis and qualitative methodology, the meaning of such movements in two districts of the disadvantaged periphery of Santa Cruz de Tenerife is examined. Although these neighborhoods present common characteristics, the research reveals an unequal scope of citizen action in the selected cases. A result which has to do with the different orientation of their citizens' struggles and has also determined for residents different possibilities of exercising their right to the city.